NuSTAR Observations of AGNs with Low Observed X-Ray to [O iii] Luminosity Ratios: Heavily Obscured AGNs or Turned-off AGNs? - Saade, M. Lynne; Brightman, Murray; Stern, Daniel; Malkan, Matthew A.; Garcia, Javier (Astrophysical Journal, 2022)
Type 2 active galactic nuclei (AGNs) show signatures of accretion onto a supermassive black hole through strong, high-ionization, narrow emission lines extended on scales of hundreds to thousands of parsecs, but they lack the broad emission lines from close in to the black hole that characterize type 1 AGNs. The lack of broad emission could indicate obscuration of the innermost nuclear regions, or could indicate that the black hole is no longer strongly accreting. Since high-energy X-rays can penetrate thick obscuring columns, they have the power to distinguish these two scenarios. We present high-energy NuSTAR observations of nine Seyfert 2 AGNs from the Infrared Astronomical Satellite 12 mu m survey, supplemented with low-energy X-ray observations from Chandra, XMM-Newton, and Swift. The galaxies were selected to have anomalously low observed 2-10 keV luminosities compared to their [O iii] optical luminosities, a traditional diagnostic of heavily obscured AGNs, reaching into the Compton-thick regime for the highest hydrogen column densities (N (H) > 1.5 x 10(24) cm(-2)). Based on updated [O iii] luminosities and intrinsic X-ray luminosities based on physical modeling of the hard X-ray spectra, we find that one galaxy was misclassified as type 2 (NGC 5005) and most of the remaining AGNs are obscured, including three confirmed as Compton thick (IC 3639, NGC 1386, and NGC 3982). One galaxy, NGC 3627, appears to have recently deactivated. Compared to the original sample that the nine AGNs were selected from, this is a rate of approximately 1%. We also find a new X-ray changing-look AGN in NGC 6890.
CRIS-Team WoS Importer:2022-09-23